Soil Characteristics under Sal (Shorea robusta) in Tarai Region of the North-eastern Himalayas - Banerjee, S. K.; Nath, S.; Singh, Balvinder; Das, P. K.; Gangopadhyay, S. K. (Indian Forester, 1989)
The nature and properties of some sal (Shorea robusta) growing soils in the tarai region of North-eastern Himalayas were studied in order to evaluate the characteristic of the soils supporting the species It was found that since sal is growing well in this area, the characteristics and nature of the soils should be favourable for the growth and development of the species Ranges of Some Of the soil sutributes suitable for the optimum growth of the species under more or less similar climatic conditions were assessed.